Coming to Claim Crip: Disidentification with/in Disability Studies - Schalk, Sami (Disability Studies Quarterly, 2013)
This creative-critical paper combines creative non-fiction and theory to trace one non-disabled scholar’s personal experience with disability studies as a field and a community. Using disidentification and crip theory, this paper theorizes the personal, political, and academic utility of identifying with crip as a nondisabled, fat, black, queer, female academic. This crip identification then undergirds and informs the researcher’s scholarship in and relationship to disability studies as a field. Specifically referencing the Society for Disability Studies dance as a potential space of cross-identification, this paper suggests that disidentification among/across/between minoritarian subjects allows for coalitional theory and politics between disability studies and other fields, particularly race/ethnic and queer/sexuality studies. Keywords: crip, identity, queer theory, race